Development of nifedipine isosteres: an integrated approach to the design, synthesis, and biological assessment of calcium channel blockers - Zohny, Yasser M.; Awad, Samir M.; Alsaidan, Omar; Rabie, Maha A. (Frontiers in Chemistry, 2025)
This study reports the synthesis of a series of calcium channel blockers via Biginelli’s reaction. The core dihydropyridine (DHP) scaffold, an isostere of nifedipine, was synthesized using three aldehydes incorporated with trifluoromethyl (–CF3) substitutions at the ortho, meta, and para positions. The resulting series (4a–c to 9a–c) was evaluated for antihypertensive and calcium channel-blocking activities in male and female rats, administered intraperitoneally. Among the synthesized compounds, the ortho-substituted derivatives (4a, 7a, 8a, and 9a) demonstrated the highest antihypertensive activity, exhibiting approximately 30% efficacy relative to nifedipine. These compounds also displayed IC50 values comparable to nifedipine and were further assessed for binding affinity with 6M7H and 4MS2 through molecular docking studies. The final DHP derivatives were amides, synthesized through reactions with aniline, 4-methylaniline, and 4-nitroaniline. Notably, compound 9a exhibited the highest docking score against both tested receptor proteins, highlighting its potential for further investigation.